Image retrieval based on hierarchical gabor filters - Andrysiak, Tomasz; Choraś, Michał (Zielona Góra: Uniwersytet Zielonogórski)
Content Based Image Retrieval (CBIR) is now a widely investigated issue that aims at allowing users of multimedia information systems to automatically retrieve images coherent with a sample image. A way to achieve this goal is the computation of image features such as the color, texture, shape, and position of objects within images, and the use of those features as query terms.
Keywords: Gabor filters; image retrieval; texture feature extraction; hierarchical representation